2021
DOI: 10.1016/j.aprim.2021.102024
|View full text |Cite
|
Sign up to set email alerts
|

Validación del RUDAS como instrumento de cribado de población con demencia en atención primaria

Abstract: Objetivo Validar la escala Rowland Dementia Assessment Scale (RUDAS) como instrumento de cribado de deterioro cognitivo y demencia en atención primaria (AP). Es un test breve, válido para población con bajo nivel educativo formal y fácilmente traducible en entornos multiculturales. Diseño Se realizó un estudio epidemiológico descriptivo, de corte transversal, con seguimiento a los 5 años. Emplazamiento Centro de sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The use of RUDAS has been recommended in primary health care (PHC) 22 due to its characteristics of being an easy and quick administration instrument. The average application time in this study was 5 minutes and 76 seconds, which is lower than the average reported in other works 10 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of RUDAS has been recommended in primary health care (PHC) 22 due to its characteristics of being an easy and quick administration instrument. The average application time in this study was 5 minutes and 76 seconds, which is lower than the average reported in other works 10 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this continues to be a subject of research. It has been recommended for public health use due to its easy and quick application 22 .…”
Section: Introductionmentioning
confidence: 99%